Three new polar species of Sternaspis Otto, 1821 (Polychaeta: Sternaspidae) - Salazar-Vallejo, Sergio I. (Zootaxa, 2014)
Two sternaspid species, Sternaspis fossor Stimpson, 1853 and S. scutata (Ranzani, 1817), have been recorded from many localities including polar or subpolar environments. The study of the collections of five major institutions cannot confirm their presence in high latitudes. On the contrary, the specimens are regarded as different, undescribed species, and are herein described as one from Arctic environments, S. buzhinskajae n. sp., and two others from Antarctic localities: S. monroi n. sp., and S. sendalli n. sp. A key to identify all Sternaspis species is included.